Teaching Students with Down Syndrome: Perspectives of Special School Teachers and Psychologists - Humayoun Amjad, Yaar Muhammad (JIE, 2024)
Imparting education to students with Down syndrome is a difficult process since it requires the use of a variety of pedagogical strategies. This study used qualitative case study method and aimed to develop an understanding of the learning difficulties faced by students with Down syndrome through the perspectives of special school teachers and psychologists. This study also aimed to understand the pedagogical practices used by teachers to manage the learning difficulties of students with Down syndrome. The criterion sampling technique was used to select participants. Data were gathered through a self-constructed semistructured interview guide containing seven dimensions. Qualitative content analysis of these seven dimensions clearly showed that teachers and psychologists perceived that students with Down syndrome certainly face many problems and hurdles in their learning such as lack of required skills, low IQ level, memory storage issues, communication problem, behavior problems, passivity, and distraction issues of students with Down syndrome. Moreover, the findings also showed that these teachers and psychologists employ a variety of pedagogical strategies to teach and manage students with Down syndrome. However, some aspects need to be addressed to make the education of these students effective.